THE EFFECT OF THE ANGLE AND DIMENSIONS OF A CROSS-SECTION SPECIMEN ON THE TORSIONAL STRENGTH OF AISI 1020 SQUARE STEEL SHAFT - Bima Cahya Maula Dana; Syamsul; Hangga Wicaksono; Kris Witono (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The unknown torsional strength due to the inconsistency of the angles and dimensions of the square cross-section of AISI 1020 steel specimens in the torsion test is the problem encountered. The research method included: preparation of square AISI 1020 steel specimens measuring 6 mm x 6 mm x 160 mm, measurement of 2 diagonal angles of the cross section of the specimen and dimensions of the cross section at 5 observation points along the specimen receiving torsion loads, torsion testing of specimens, analysis of torsion test results data, and drawing conclusions. The results of the study affect the angle and dimensions of the specimen cross-section on the torsional strength of the AISI 1020 steel square shaft which has a greater value at the angles of 89o and 91o than 90o which with an angle of 89o at dimensions of 5.96 mm x 5.96 mm has a torsional strength of 412 MPa, while at an angle of 90o with dimensions of 5.96 mm x 5.96 mm it has a torsional strength of 359 MPa, and for an angle of 91o in dimensions of 5.95 mm x 5.95 mm has a torsional strength of 402 MPa. The average torsional strength is achieved in the range of 351 to 397 MPa, at an angle of 89o the torsional strength increases by 46 MPa or around 13.1 %, and at an angle of 91o the torsional strength increases by 43 MPa or around 12.3%.